Az Érdy-kódex De tempore részének exemplumai - Bartók, Zsófia Ágnes (Studia Litteraria, 2013)
The essay describes the different types of exempla in the De Tempore part of the Codex Érdy. The classification is based on the texts’ relations to their source. In the first place, the codex contains exempla which are very closely attached to their source, to the sermons of Pelbartus de Temesvár. Secondly, there are exempla that also follow a sermon of Pelbartus but are influenced by other traditions, too. In other cases it can be argued that the compilator of the Codex Érdy used Pelbartus but he transposed the exemplum into a different context. Finally, some of the exempla supposedly have nothing to do with the codex’s main source, that is, to Pelbartus, since they must have been taken from other unknown sources. By the comparison of the Hungarian and the Latin texts, we can understand more profoundly the methods of the anonymous compilator and we can reveal the mechanisms that affect the compilation of a Hungarian sermon of that time.